English Language Learning Management in Islamic Religious Activities at Central Course Tangerang - Mariyanah, Siti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to analyze (1) the planning of English language learning and the facilitation of Islamic religious activities at the Central Course Tangerang, (2) the implementation of English language learning and the facilitation of Islamic religious activities at the Central Course Tangerang, and (3) the assessment of English language learning and the facilitation of Islamic religious activities at the Central Course Tangerang. The research utilized a descriptive qualitative method with a case study design. The main subjects in this study were the educational coordinator, teaching tutors, and course participants, while additional data was provided by the course director and administrative staff. Data collection techniques included observation, interviews, and documentation. The validity of the data was ensured through source triangulation and technique triangulation. The results indicated that the Central Course Tangerang applied learning management functions effectively. (1) Learning planning was developed by the educational coordinator in collaboration with tutors, and the analysis of lesson plans met the required standards, including objectives, strategies, teaching materials, media, and methods. (2) The learning process was conducted effectively, aligning with the goals outlined in the lesson plan. (3) The assessment, as the final stage of learning, was carried out appropriately, with assessment types adjusted to the teaching materials, including both written and non-written evaluations. Furthermore, the facilitation of Islamic religious activities was well-organized, with daily and weekly schedules, as well as during Islamic holidays (PHBI).